PHM-based wiring system damage estimation for near zero downtime in manufacturing facilities. (April 2019) - Lee, Jinwoo; Kwon, Daeil; Kim, Namhun; Lee, Changyong
Highlights: A PHM-based means for wiring system maintenance planning was introduced. Changes in digital signal characteristics could detect multiple failure modes. The proposed approach should enable improved system maintenance planning. Abstract: Wiring system is usually installed in manufacturing facilities to construct a data network. During the operation of the manufacturing facility, environmental and operational stress conditions may degrade material properties of the wires, and cause wire faults and failures, which deteriorate the electrical connection within and out of the wiring system. Conventional health monitoring approaches, such as time domain reflectometry, have been actively developed to detect wire faults with improved accuracy. However, these approaches often require external devices connected with the wiring system, which may interfere system operation, and lead to inevitable system downtime of the facility for maintenance. In order to eliminate unnecessary system downtime, alternative means for wiring health monitoring is required. This paper discusses a prognostics and health management(PHM)-based means required for wiring system maintenance planning using digital signal characteristics. Degradation of wire material property causes impedance discontinuities, which in turn deteriorate the integrity of the transmitted signal. The extent of wire damage can be detected by monitoring the integrity of digital signal. In order to demonstrate the ability of digital signal for wire health monitoring, wire abrasion tests were performed with continuous monitoring of digital signal characteristics. The test results showed the changes in digital signal characteristics and the extent of wire damage were highly correlated, and could detect multiple failure modes of wiring system without requiring additional sensing or monitoring devices. Thus, digital signal based wiring health monitoring should enable improved system maintenance planning towards near zero downtime.